Difference in out-of-school physical activity patterns, sedentary behavior, and health-related fitness in relation to mathematics achievement among school-aged children: a cross-sectional study - Hermassi, Souhail; Dhahbi, Wissem; Jebabli, Nidhal; Alneama, Abdulla; Ketelhut, Sascha; van den Tillaar, Roland (Frontiers in Education, 2025)
AimThis study examined differences in health-related fitness, physical activity patterns, and sedentary behavior among Qatari schoolchildren, classified by their mathematics achievement levels.MethodsNinety-eight schoolchildren (age: 12.1 ± 0.5 years; height: 1.58 ± 0.9 m; body mass: 50.5 ± 13.6 kg; Body mass index: 20.6 ± 4.7 kg/m2) participated in this cross-sectional study. Based on their mathematics grade point average (GPA), participants were classified into two achievement levels Excellent level in mathematics (90–100; n = 49), and Good level in mathematics (70–79; n = 49). Assessments included anthropometric measurements, physical performance tests (medicine ball throw, postural stability, and handgrip strength), and out-of-school physical activity levels measured using the International Physical Activity Questionnaire-Short Form.ResultsSignificant differences between the achievement levels were detected in postural stability (p < 0.001, ηp2 = 0.137), with excellent pupils demonstrating better balance (boys: 2.09 ± 0.36 s, girls: 2.05 ± 0.45 s) versus good level pupils (boys: 1.71 ± 0.55 s, girls: 1.69 ± 0.51 s). Total physical activity levels displayed substantial sex-based variations (p < 0.001, ηp2 = 0.188), with boys showing higher activity levels across achievement groups. Sedentary behavior also differed significantly between achievement levels (p < 0.001, ηp2 = 0.166), with lower-achieving students accumulating more sitting time. Mathematics achievement level predicted 23.7% of the variance in sedentary behavior (R2 = 0.237, p = 0.002).ConclusionThe findings demonstrate significant associations between mathematics achievement level, health-related fitness, and activity patterns among Qatari schoolchildren. The strong relationship between postural stability and mathematics performance, along with the inverse association between sedentary behavior and mathematics achievement level, suggests the presence of shared underlying mechanisms and cognitive abilities that may influence both physical and academic outcomes.